Assessment of Climate Change over the Indian Region A Report of the Ministry of Earth Sciences (MoES), Government of India - Krishnan, R.; Sanjay, J.; Gnanaseelan, Chellappan; Mujumdar, Milind; Kulkarni, Ashwini; Chakraborty, Supriyo (Springer Nature Singapore : Imprint: Springer, 2020)
This open access book discusses the impact of human-induced global climate change on the Indian subcontinent and regional monsoon, the adjoining Indian Ocean and the Himalayas. It also examines the regional climate change projections based on the climate models used by the IPCC Fifth Assessment Report (AR5) and national climate change modeling studies using the IITM Earth System Model (ESM) and CORDEX South Asia datasets. The IPCC assessment reports, published every 6-7 years, provide important reference material for major policy decisions on climate change, adaptation, and mitigation. While the IPCC assessment reports largely provide a global perspective on climate change, they offer limited information on the regional aspects of climate change. Regional climate change effects over the Indian subcontinent, especially relating to the Indian monsoon, are unique to the region, and in particular, the climate in this region is shaped by the Himalayas, Western Ghats, the Tibetan Plateau, the Indian Ocean, Arabian Sea, and Bay of Bengal. Climatic variations in this region are influenced by (a) regional-scale interactions between the atmosphere, ocean, land surface, cryosphere and biosphere on different time scales, (b) remote effects from natural phenomena such as the El Nino / Southern Oscillation, North Atlantic Oscillation, Indian Ocean Dipole, and Madden Julian Oscillation, and (c) human-induced climate change. This book presents policy-relevant information based on robust scientific analysis and assessments of the observed and projected future climate change over the Indian region.